Adoção do sistema de pluralidade sindical como forma de valorização e reconhecimento incondicional da liberdade sindical no Brasil - Príncipe, Carlos Eduardo (2018)
The present thesis aims to demonstrate that the Brazilian trade union system based on the single trade union principle is "frozen" in time and inconsistent with the plural trade union model which is recommended by democratic systems, and which has made full freedom of association real as a mainstay of the working class’s expression. Thus, through a bibliographical research, a historical retrospective was conducted of the birth and development of the Brazilian trade union movement up to the advent of the 1988 Federal Constitution, which marked the definitive break from the military dictatorship’s "years of lead", and consolidated the democratic regime in our country, but – upon a decision by the Constitutional Assembly – preserved the single trade union model, and did not opt for broad union freedom. Thus, a statistical view of unionization in Brazil – based on IBGE data - is provided, and a comparison is made with union costs. In parallel, the importance of the International Labor Organization and its main conventions is described with highlights on the trade union structure in other countries, which could serve as a paradigm for implementation of a plural trade union system. Then, a survey was conducted on the advances and retrocessions that occurred after the 1988 Constitution was enacted, both in the legislative and judicial fields, and the legal advances made under the recently enacted "Labor Reform" Law. The examination of this institutional scenario points to the conclusion that, in view of the democratic principles set forth in the Constitution, the adoption a plural trade union system imposes itself as way of valuing and unconditionally recognizing trade union freedom of association